Activities of daily living mediate the association between balance and falls in middle aged and older adults - Jiaran Jiang; Quan Zhou; Chuanxia Zhang; Keer Cong (Scientific Reports)
Abstract Falls constitute a significant public health issue affecting middle-aged and older adults.The consequences of falls extend beyond physical injuries and compromised quality of life to encompass psychological and socioeconomic dimensions. Investigate the mediating role of Activities of Daily Living (ADL) in the relationship between balance ability and falls. This study utilized data from the 2015 China Health and Retirement Longitudinal Study (CHARLS). Balance ability was assessed using the Short Physical Performance Battery (SPPB), while ADL were evaluated through the CHARLS ADL questionnaire. Demographic factors and health-related indicators were incorporated as covariates.Data analysis was conducted in StataMP 17, employing chi-square tests, independent samples t-tests, correlation analysis, and parallel mediation analysis. Results revealed significant between-group differences in gender, marital status, and education level (all p < 0.001) between fallers and non-fallers.Females accounted for 67.6% of fall incidents, surpassing the male proportion (32.3%). Mediation analysis identified a significant direct effect of balance ability on falls (c’ = 0.002, p < 0.05), with ADL demonstrating partial mediation (a*b = 0.019, 95% CI: 0.014–0.026). Our findings demonstrates significant associations between falls, balance ability, and ADL disability. Activities of daily living (ADL) disability partially mediates the association between balance ability and falls. However, the observed associations were modest in strength, and the study’s cross-sectional design, reliance on self-reported data, and high baseline balance scores in the sample limit causal inference and generalizability. These results highlight the multifactorial nature of falls and underscore the importance of integrated prevention strategies that address both physical function and other potential mediators.